ANALISIS PENDEKATAN SISTEM DALAM EKONOMI ISLAM (Sebuah Pemikiran Maqashid Al-Syariah as Philosophy of Islamic Law Jasser Auda) - Matnin; Saiban, Kasuwi; Munir, Misbahul (DPPM Universitas Pelita Bangsa, 2022)
The purpose of this study is to analyze the systems approach in Islamic economics based on maqashid al sharia thinking using the system philosophy offered by Jasser Auda. According to him, there are at least two approaches that need to be mastered professionally at the same time, namely first, approaches that are closely related to the dimensions of time and history and second, approaches that are closely related to philosophical concepts and thoughts. The basic concepts used by Jasser Auda in the Systems approach and analysis in Maqasid Syariah as a philosophy of Islamic law include looking at the problem as a whole (Wholeness), always being open to the possibility of improvement and refinement (Openness), interrelated-Hierarchy. , involving various dimensions (Multidimensionality) and prioritizing and prioritizing the main goal (Purposefulness). The approach in this research is descriptive qualitative. The analysis technique used is content analysis (content analysis). Content analysis is simply defined as a method for collecting and analyzing the content of a text. The original of this research on Islamic economics within the framework of a systems philosophy approach is Cognition (Cognitive Nature), Towards Holism, Towards Openness/Wholeness,. Interrelated Hierarchy, Multi-dimensionality, Purposefulness/Intentions.